2012
DOI: 10.1136/annrheumdis-2011-200947
|View full text |Cite
|
Sign up to set email alerts
|

Is there a sex bias in prescribing anti-tumour necrosis factor medications to patients with rheumatoid arthritis? A nation-wide cross-sectional study

Abstract: For women with rheumatoid arthritis, treatment with anti-TNF therapy was initiated at a higher level of subjective disease activity than for men, but at the same level of physician-reported disease activity. These data imply that patients' subjectively experienced disease activity may be discounted in the treatment decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
5
14
1
2
Order By: Relevance
“…However, we did not find such evidence, and this is in line with similar studies [39]. The differences in TJC and SJC are not large, they could nonetheless be important when studied at group level.…”
Section: Discussionsupporting
confidence: 89%
“…However, we did not find such evidence, and this is in line with similar studies [39]. The differences in TJC and SJC are not large, they could nonetheless be important when studied at group level.…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with other European registries in the PsoNet group, showing a notable dominance of men with 68% in the Netherlands, 67% in Italy, 66% in Denmark, 63% in Spain and 60% in Germany [10]. There is an active discussion whether women are discriminated by not receiving the same quantity of high-priced drugs as men in several fields of medicine [11], [12]. Previous studies indicate that men receive systemic or UV treatment for psoriasis in greater extent than women [13], [14].…”
Section: Introductionsupporting
confidence: 85%
“…Thus, the only DAS28 component that significantly differed during the longitudinal analysis was the TJC. Previous studies in RA have shown higher disease activity in women as measured by the DAS28, TJC score and patient global assessment, [15][16][17] contrasting with similar radiographical progression. 4 16 Gender differences in pain perception and assessment reported in RA as well as in spondyloarthritis 18 19 may explain this dissociation.…”
Section: Discussionmentioning
confidence: 99%